2000
DOI: 10.15760/etd.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Wiki-based Collaborative Writing on English L2 Learners' Individual Writing Development

Abstract: Although the benefits of group and pair work in the second language (L2) classroom have been extensively studied, most documented research has focused on the use of oral tasks and spoken interaction between learners. Recently however, researchers have begun to investigate the advantages of collaboration on written work. More specifically, with the advancements in computer technology and webbased collaborative platforms like wikis, there has been a growing awareness of the educational possibilities of wikis to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…In recent years, the focus of ESL writing research is in four areas: genre theory, cooperative writing, grammar correction and individual differences, among which grammar correction has always been a hot topic. In addition, academic writing, corpus-based approach (Aull, 2015; Romero-Trillo, 2014), writer's identity (Ouellette, 2008;Ricento, 2005), as well as cooperative writing based on Wiki (Caruso, 2014;Chao & Lo, 2011;Elola & Oskoz, 2010), have gradually become research focus in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the focus of ESL writing research is in four areas: genre theory, cooperative writing, grammar correction and individual differences, among which grammar correction has always been a hot topic. In addition, academic writing, corpus-based approach (Aull, 2015; Romero-Trillo, 2014), writer's identity (Ouellette, 2008;Ricento, 2005), as well as cooperative writing based on Wiki (Caruso, 2014;Chao & Lo, 2011;Elola & Oskoz, 2010), have gradually become research focus in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…So, OCW did not affect the range of spoken words. It might result from students' using more complex and uncommon vocabulary as their vocabulary knowledge grows (Caruso, 2014). On the third measure, fluency, the higher mean scores of W and T/S in the post-test indicated that students wrote longer texts and used more T-units per sentence.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, it has been shown that wikis have a positive effect on the educational outcomes of various fields such as pharmacy (Thompson & O'Bryant, 2014), nursing (Kardong-Edgren, 2009), statistics (Neumann & Hood, 2009), software engineering (Ras & Rech, 2009), information and communication technologies (Kear et al, 2010). It is seen that wikis have positive contributions as collaborative writing tools, especially in foreign language writing education (Alshumaimeri, 2011;Wong et al, 2011;Caruso, 2014;Li et al, 2014;Al-Johali, 2019;Khan and Hameed, 2021). Using wiki technology in second language writing education positively contributes to writing motivation (Çelik and Aydın, 2021).…”
Section: Wikis and Blogsmentioning
confidence: 99%